(untitled) (Orthodontic Journal of Nepal, 2024)
Background: Various factors affect shear bond strength, and several methods can be used to enhance the bond strength. Aims and Objectives: The aim of this study was to evaluate and compare the shear bond strengths after various surface treatments of bonding bases. Materials & Methods: For this research, 275 extracted human fist and second premolar teeth were cleaned and stored in artificial saliva (Saleva). The teeth were randomly divided into control and experimental groups. The groups were subdivided according to the types of brackets used (metal, ceramic and recycled metal brackets). Metal brackets (Ormco) and ceramic brackets (Ortho Organizer) were bonded on the buccal surfaces of the mounted premolars after respective surface treatments. Samples were stored in an incubator for 48 hours. The shear bond strength was evaluated using a Universal Testing Machine (UTM). Kruskal-Wallis test and Mann-Whitney U test were performed for comparison of bond strengths. Results: Ceramic brackets showed significantly higher shear bond strength than metal brackets, with a p-value of 0.004. Within ceramic brackets, sandblasting of the tooth surface and bracket base resulted in significantly higher bond strength than other surface treatments. Conclusion: Our study found that double primer coating and sandblasting are the surface treatments of choice to increase bond strength, and the least accepted method for the surface treatment is diamond bur grinding. Further surface studies are required to assess the effect of sandblasting on bonding bases.